Current advances of transition metal dichalcogenides in electromagnetic wave absorption: A brief review - Zhang, Shijie; Li, Jiying; Jin, Xiaotian; Wu, Guanglei (International journal of minerals, metallurgy and materials, 2023)
Transition metal dichalcogenides (TMDs) show great advantages in electromagnetic wave (EMW) absorption due to their unique structure and electrical properties. Tremendous research works on TMD-based EMW absorbers have been conducted in the last three years, and the comprehensive and systematical summary is still a rarity. Therefore, it is of great significance to elaborate on the interaction among the morphologies, structures, phases, components, and EMW absorption performances of TMD-based absorbers. This review is devoted to analyzing TMD-based absorbers from the following perspectives: the EMW absorption regulation strategies of TMDs and the latest progress of TMD-based hybrids as EMW absorbers. The absorption mechanisms and component-performance dependency of these achievements are also summarized. Finally, a straightforward insight into industrial revolution upgrading in this promising field is proposed.